Model Matematika Penyebaran Virus Komputer dengan Eksistensi Programmer Virus - Meri Mulyani; Media Rosha; Riry Sriningsih (Journal of Mathematics UNP, 2021)
Abstract – On the article discussed the mathematical model SIRI (Susceptible, Infected, Recovered, and Infected) to describe the propagation behavior of computer virus under existence virus programmer. Based on the analysis, model has two the equilibrium points that are disease-free equilibrium point and endemic equilibrium point. Existence and stability of the equilibrium point was determined by the basic reproductive number. Disease-free equilibrium point always there and stable if the basic reproductive number is smaller than one, whereas endemic equilibrium point exists and stable only if the basic reproductive number is greater than one. Based on these results and a parameter analysis, the numerical simulation to illustrate the analytic results obtained.Keywords – Mathematical Model, Virus Programmer, Equilibrium Point, Stability, Basic Reproductive Number